2010
DOI: 10.1007/bf03404376
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Response Rates across Racial and Ethnic Populations

Abstract: nderstanding and reducing health disparities as well as promoting equality for ethnic or racial population health have become important priorities among researchers and governments as populations of western countries are becoming ethnically and racially diverse. For example, to date, over 5 million (16.2%) Canadians consider themselves non-White and non-Aboriginal (i.e., visible minorities) and it is estimated that this number will steadily increase over the next decade due to immigration. 1 Therefore, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…Usual mail survey response rates range from 20% to 70% depending on the population surveyed. 26 Although the relatively high response rate in our study is encouraging, we are unable to account for the opinions of nonresponders. Our response rate is significantly higher than the only other available patient survey on this topic (28.3%), 24 which we attribute to reminder postcards, clinic room posters describing the study, and the strong commitment our patients have to participating in research to help women with gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 57%
“…Usual mail survey response rates range from 20% to 70% depending on the population surveyed. 26 Although the relatively high response rate in our study is encouraging, we are unable to account for the opinions of nonresponders. Our response rate is significantly higher than the only other available patient survey on this topic (28.3%), 24 which we attribute to reminder postcards, clinic room posters describing the study, and the strong commitment our patients have to participating in research to help women with gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 57%
“…Among aging survivors of childhood cancer, it is plausible that participants in long‐term follow‐up research studies may not represent the larger underlying population of survivors in the United States, thereby potentially providing biased estimates of rates and risks that are not generalizable to all survivors. There is contradictory evidence related to differences in participation rates in observational studies by race/ethnicity . Differences in recruitment rates vary widely based on the methodological approaches used; higher minority participation rates are observed in those studies in which specific strategies are used to maximize minority participation …”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory evidence related to differences in participation rates in observational studies by race/ethnicity . Differences in recruitment rates vary widely based on the methodological approaches used; higher minority participation rates are observed in those studies in which specific strategies are used to maximize minority participation …”
Section: Discussionmentioning
confidence: 99%
“…Mailed invitations have been shown to improve the demographic representativeness of survey participants in web‐based surveys, especially when a monetary incentive is included (Dykema, Stevenson, Klein, Kim, & Day, 2012). For example, Sykes, Walker, Ngwakongnwi, and Quan (2010) found that response rates were lowest for African American respondents and highest for Latina/o American respondents, with the response rate for White respondents falling between these two groups. Therefore, similar to mail‐based surveys, response rate techniques must also be examined to ensure that survey language and content are culturally flexible (Sykes et al, 2010).…”
mentioning
confidence: 99%